Remoción de materia orgánica mediante humedales artificiales con pasto saboya (panicum máximum) y pasto elefante (pennisetum purpureum) en aguas residuales bovinas - Aguilar Gutiérrez, José David (2021)
The removal of organic matter by artificial wetlands using Savoyard grass (Panicum maximum) and elephant grass (Pennisetum purpureum) is a technique used to treat bovine wastewater. The research was carried out in the area of CIIDEA (Centre for Research, Innovation and Agricultural Development); bovine wastewater samples were taken on the grounds of the estate "Bella Aurora", Eloy Alfaro parish, Chone canton, lasting 9 months with the aim of removing organic matter by artificial wetlands with Savoyard grass (Panicum maximum) and elephant grass (Pennisetum purpureum) in bovine wastewater. Two types of pastures (Panicum Maximum and Pennisetum purpureum) were handled. The experimental unit consisted of two artificial wetlands, each artificial wetland had three repetitions, in one were transplanted 4 macollo of Savoy grass and in the other 4 macollo of elephant grass. The experimental method used was a completely random unifactorial (DCA) design, the data were analyzed through the ANOVA at 5% significance and the separation of means through the Tukey test, the Infostat free version statistical software 2020 was used. The average flow of bovine wastewater from the Bella Aurora estate, Eloy Alfaro parish in the canton chone, was 0.0289 l's. The result obtained from the sample evaluated demonstrated a high level of BOD in bovine wastewater exceeding the provisions of current regulations. Biochemical demand for oxygen showed significant differences between treatments, using Savoyard and elephant pastures as removers of organic matter in bovine wastewater, it was possible to reduce by 36.79% through Savoyard grass whose treatment cost was $237.40 and 39.96% using elephant grass at a cost of $277.90. The final cost for the implementation of an artificial wetland for the removal of organic matter for farmers and ranchers was $ 88.00 for savoy grass and $ 128.50 for elephant grass in USD / m2 of H A. So it could be suggest this technique in future research due to its low costs.